2020
DOI: 10.1108/ijchm-08-2019-0694
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nonverbal customer-to-customer interactions on customer satisfaction and loyalty intentions

Abstract: Purpose This study aims to examine the relationship among nonverbal customer-to-customer interactions (CCIs), positive and negative emotions, customer satisfaction and loyalty intentions. Design/methodology/approach The conceptual model that was developed using the stimulus-organism-response theoretical framework was tested using a sample of 583 consumers. Findings The results show that kinesics and paralanguage positively affect customers’ positive emotions while proxemics, paralanguage and physical appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 78 publications
4
39
0
1
Order By: Relevance
“…This stage is in line with the research conducted by Kandampully et al (2018), Plessis and Vries (2016) and CEM definition by Gartner (2020) that pointed to service design, experience design and interaction design, respectively. Social environmental stimuli such as nonverbal interactions of customers with each other and with employees should be considered in designing the servicescape, as suggested by Lin et al (2020). Co-creation with the customer is also consistent with the theory of “service-dominant logic” by Vargo and Lusch (2004) and the research carried out by Prahalad and Ramaswamy (2003) entitled “co-creation of experience.”…”
Section: Discussionsupporting
confidence: 70%
“…This stage is in line with the research conducted by Kandampully et al (2018), Plessis and Vries (2016) and CEM definition by Gartner (2020) that pointed to service design, experience design and interaction design, respectively. Social environmental stimuli such as nonverbal interactions of customers with each other and with employees should be considered in designing the servicescape, as suggested by Lin et al (2020). Co-creation with the customer is also consistent with the theory of “service-dominant logic” by Vargo and Lusch (2004) and the research carried out by Prahalad and Ramaswamy (2003) entitled “co-creation of experience.”…”
Section: Discussionsupporting
confidence: 70%
“…Affective experience, rarely discussed in prior literature, is identified in this study, echoing the suggestion of and Wu and Gao (2019) to emphasize the emotional experience of customers rather than purely cognitive experiences. The concept of social experience, proposed in this study, is related to but beyond human interaction (Lin et al, 2020;Walls, 2013), staff relational/interactional experience (Ren et al, 2016) and humanity clues (Chepngetich et al, 2019) as stated in prior studies. It shall include customer's self-esteem and social self-image, which are rarely mentioned in other studies.…”
Section: Discussionmentioning
confidence: 90%
“…Customer satisfaction and loyalty are paramount for a firm's performance, yet their exact relationship is not always clear (Baumann et al, 2017). The tourism and hospitality sector have long experienced the impacts of positive or negative experiences in customers' behavioural predispositions (Heung and Lam, 2003;Lin et al, 2020). Yet, Baumann et al (2012) identified that the relationship between the two concepts is rather non-linear, suggesting that customers' satisfaction after a poor experience is not directly converted into loyalty nor clearly predicted behavioural intentions.…”
Section: Ijchm 339mentioning
confidence: 99%